PENGARUH KEPRIBADIAN NEUROTIK TERHADAP MOTIVASI DAN PRESTASI BELAJAR PENDIDIKAN AGAMA KRISTEN SISWA DI SMP NEGERI 8 MANADO - Jeane M. Tulung; Febri Manoppo (Jurnal Ilmiah Wahana Pendidikan, 2022)
The ipurpose iof ithis istudy iis ito ifind iout iand idescribe ithe ipresence ior iabsence iof ineurotic ipersonality iinfluences ieither ion ilearning imotivation ior ilearning iachievements iof iChristian iReligious iEducation ifrom istudents iat iSMP iNegeri i8 iManado. iThis iresearch iis ia iquantitative iresearch iwith ia icausal iassociative imethod icarried iout iat iSMP iNegeri i8 iManado iin i2021. Data iis icollected iusing iquestionnaires ior iquestionnaires iand idocumentation. iQuestionnaires iare iused iby iresearchers ito iobtain idata ion ineurotic ipersonality iand ilearning imotivation, iwhile idocumentation iis ito iobtain idata ion ilearning iachievements iof iChristian iReligious iEducation. iData ianalysis itechniques iused ito itest ithe ihypothesis iof ithis istudy ior ito idetermine ithe ipresence ior iabsence iof ithe iinfluence iof ineurotic ipersonality ion ithe imotivation iand iachievement iof ilearning iChristian iReligious iEducation, inamely iusing iChi iSquared iand ito idetermine ithe imagnitude iof ithe idegree iof iinfluence iof iteacher imotivation ion imotivation iand ilearning iachievement iof iChristian iReligious iEducation, inamely iusing ithe iContigency iCoefficient. The iresults iof ithe ineurotic ipersonality iquestionnaire iwere ifound ithat i61 iclass iIX istudents iwho iwere irespondents ito ithis istudy, ias imany ias i10 istudents i(16.40%) ihad ihigh ineurotic ipersonality isigns, i40 istudents i(65.57%) iin ithe imedium icategory iand i11 istudents i(18.03%) iin ithe ilow icategory. iIn ithe ilearning imotivation iquestionnaire, i61 irespondents iwere ifound, ias imany ias i14 istudents i(22.96%) ihad ihigh ilearning imotivation, i40 istudents i(65.57) iin ithe imedium icategory iand i7 istudents i(11.47%) iin ithe ilow icategory. iMeanwhile, ifor ilearning iachievement, ias imany ias i31 istudents i(50.82%) ihad igood ilearning iachievements, i17 istudents i(27.87%) iin ithe isufficient icategory iand i13 istudents i(21.31%) iin ithe iless icategory. Based ion ithe ianalysis iof idata ithat iresearchers icalculated, iit ican ibe iseen ithat ithere iis ian iinfluence iof ineurotic ipersonality ion ilearning imotivation iand ilearning iachievement iof iChristian iReligious iEducation istudents iat iSMP iNegeri i8 iManado. iTherefore, ithe ihypothesis ithat ithe iresearcher iproposed iwas iaccepted, inamely ineurotic ipersonality iaffects ithe imotivation ito ilearn iChristian iReligious iEducation ifor igrade iIX istudents iand ineurotic ipersonality iaffects ithe ilearning iachievement iof iChristian iReligious iEducation ifor igrade iIX istudents.